2000
DOI: 10.1056/nejm200006083422303
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Paracentesis and Transjugular Intrahepatic Portosystemic Shunting in Patients with Ascites

Abstract: In comparison with large-volume paracentesis, the creation of a transjugular intrahepatic portosystemic shunt can improve the chance of survival without liver transplantation in patients with refractory or recurrent ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
332
6
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(361 citation statements)
references
References 28 publications
9
332
6
14
Order By: Relevance
“…The 27% 90-day survival rate for the current study patients with ascites is far below the reported range of 1-year transplantation-free survival rates of 41-69% for patients with ascites who underwent TIPS. 4,41 Therefore, we caution the use of TIPS in the subgroup of patients who have concomitant malignancies and hepatogenic ascites and in the subgroup of patients who have hepatic primary malignancies, regardless of indication.…”
Section: Discussionmentioning
confidence: 99%
“…The 27% 90-day survival rate for the current study patients with ascites is far below the reported range of 1-year transplantation-free survival rates of 41-69% for patients with ascites who underwent TIPS. 4,41 Therefore, we caution the use of TIPS in the subgroup of patients who have concomitant malignancies and hepatogenic ascites and in the subgroup of patients who have hepatic primary malignancies, regardless of indication.…”
Section: Discussionmentioning
confidence: 99%
“…There have been 4 randomized controlled trials comparing TIPS versus large-volume paracentesis as a treatment for refractory ascites. [50][51][52][53] In the first study, none of the Child-Pugh class C patients eliminated their ascites, and their overall survival was significantly worse in the TIPS group. 50 Thus, TIPS is generally considered to be contraindicated in Child-Pugh class C patients.…”
Section: Transjugular Intrahepatic Portosystemic Shunt (Tips)mentioning
confidence: 99%
“…What could be the source of this disparity? One explanation is a methodological differences between the current study and prior studies [2][3][4]8]. Other studies censored patients who underwent OLT, such that the date of transplantation was considered the last day of follow-up and not counted as an event.…”
mentioning
confidence: 92%
“…
Although a survival benefit following transjugular intrahepatic portosystemic shunt (TIPS) creation for variceal bleeding [1] and ascites [2,3] has been reported in randomized controlled trials (RCTs) in cirrhotic patients, clinical outcomes after TIPS placement in patients with late-stage liver disease and high Model for End-Stage Liver Disease (MELD) scores remain controversial. The MELD score was originally created to predict the survival after TIPS placement in patients with cirrhosis; by intention, a high MELD score predicts poor survival after TIPS [4].
…”
mentioning
confidence: 99%